Changes in menopause-specific quality of life between women with transdermal estradiol versus oral estrogens: results of a randomized controlled trial - Ruiyi Tang; Yubo Fan; Xiangyan Ruan; Zhifen Zhang; Mulan Ren; Jie Wu; Kuanyong Shu; Huirong Shi; Meiqing Xie; Shulan Lv; Xin Yang; Qi Yu; et al. (Gynecological Endocrinology)
Objective To compare the efficacy of oral and transdermal estrogens in improving the quality of life in perimenopausal and recently postmenopausal women.Methods 257 women aged 40-55 years, within three years after their final menstrual period were randomized to receive transdermal oestrogel (t-E2) (n = 128) or oral estradiol valerate (o- E2V) (n = 129; both with micronized progesterone 200 mg for 14 days each month). Menopausal symptoms were recorded at screening and at 4, 12, and 24 weeks post-randomization. Menopausal symptoms were evaluated using the Menopause-Specific Quality of Life (MENQOL) questionnaire.Results Significant improvements of MENQOL scores were observed in both groups compared with baseline. The decrease of MENQOL scores after treatment showed almost no difference between the two groups (p > 0.05) except the VMS domain which indicated a better result in oral estrogen group after 24 weeks.Conclusions This study showed that both transdermal and oral estrogens were highly effective in relieving the overall menopausal symptoms for recently-menopausal women, with little difference in treatment efficacy between the two routes.